Legal Protection for Homebuyers in Cases of Developer Default on Guarantees Issued Without Prior Notification (A Case Study of Bekasi District Court Decision Number: 239/Pdt.G/2020/PN Bks) - Fikrie, Safina Nabila; Sulastri, Sulastri (Jurnal Daulat Hukum, 2024)
With the progression of time, the demand for housing has significantly increased, motivating various parties to develop businesses in the property sector, particularly in housing. However, in pursuing this business, developers sometimes fail to fulfill their obligations, as illustrated in the Bekasi District Court Decision Number 239/Pdt.G/2020/PN Bks. The purpose of this scientific article is to examine the legal protection available to home buyers against breach of contract by developers and to identify possible courses of action buyers can take to secure ownership rights from non-compliant developers. This article utilizes a normative juridical research method through legislative and case-based approaches. The issues addressed are the legal protections available for home buyers in cases of developer breach of contract and the remedies available to buyers for securing their ownership rights when developers fail to meet contractual obligations. The findings indicate that legal protection for home buyers can be based on the Consumer Protection Law and the Indonesian Civil Code. Buyers have several possible actions, such as demanding that developers fulfill their obligations as per the court ruling, seeking compensation for damages incurred, and reporting the issue to the Ministry of Public Works and Public Housing (PUPR), which has the authority to impose administrative sanctions on developers.